Enhancement of immune response induced by DNA vaccine cocktail expressing complete LACK and TSA genes against Leishmania major. Issue 4 (18th September 2012) - Ghaffarifar, Fatemeh; Jorjani, Ogholniaz; Sharifi, Zohreh; Dalimi, Abdolhossein; Hassan, Zuhair M.; Tabatabaie, Fatemeh; Khoshzaban, Fariba; Hezarjaribi, Hajar Ziaei
Abstract : Leishmaniasis is an important disease in humans. Leishmania homologue of receptor for Activated C Kinase (LACK) and thiol specific antioxidant (TSA) as immuno‐dominant antigens of Leishmania major are considered the most promising molecules for a DNA vaccine. We constructed a DNA cocktail, containing plasmids encoding LACK and TSA genes of Leishmania major and evaluated the immune response and survival rate in BALB/c mice. IgG and Interferon gamma values were noticeably increased in the immunized group with DNA cocktail vaccine, which were significantly higher than those in the single‐gene vaccinated and control groups (p < 0.05) following the immunization and after challenging with Leishmania major . Interleukin 4 values were decreased in all immunized groups, but only in DNA vaccine cocktail and single‐gene vaccination with pc‐LACK there were statistical differences with control groups (p > 0.05) . The immunized mice with the cocktail DNA vaccine presented a considerable reduction in diameter of lesion compared to other groups and a significant difference was observed (p < 0.05) in this regard. The survival time of the immunized mice with the cocktail DNA vaccine was significantly higher than that in the other groups (p < 0.05) after their being challenged with Leishmania major . The findings of this study indicated that the cocktail DNA vaccine increased the cellular response and survival rate and induced protection against infection with Leishmania in the mice.